Blogs, political discussion and the 2005 New Zealand general election : a thesis presented in partial fulfilment of the requirements for the degree of PhD in Communication at Massey University - Hopkins, Kane (Massey University, 2009)
Communication technologies have altered the way people engage in political discourse. In recent years the internet has played a significant role in changing the way people receive political information, news and opinion. Perhaps the most significant difference as a result of advancements in communication and internet technology is how people participate in discussions and deliberate issues that are important to them. The 2005 New Zealand General Election fell at a time when functionality and access to fast and affordable internet allowed people to develop their own information channels and also determine how, where and to what level they participated in debate and commentary on election issues. The aim of this thesis is to examine how blogs were used to discuss political issues during the 2005 New Zealand General Election campaign period through the use of three inter-related methodologies. The methodologies used in the research are content analysis, interviews and a case study. Four blogs and the comments sections are analysed by way of content analysis for adherence to the rules of communicative interaction within the public sphere. Interviews were conducted with a number of people who blogged during the 2005 election campaign, to develop an understanding of their experiences and perceptions of the role blogging played in the election. A case study of politician and blogger Rodney Hide examines the role blogs play as a communication tool for politicians and the how they change the relationship between politician and voter. An explosion of academic literature in recent years has looked at the participative and deliberative nature of the internet and blogs as having opened new spaces and what implications that may have for democracy. Jurgen Habermas' seminal book, The Structural Transformation of the Public Sphere, provides the theoretical basis for this thesis and the foundation for academic writing in this area. Habermas developed the normative notion of the public sphere as a part of social life where citizens exchanged views and opinions on matters of importance to the common good, so that wider public opinion can be formed.
Keywords: Blogs; Political campaigns; 2005 general election, New Zealand; Communication; Internet; General elections, New Zealand; Fields of Research::420000 Language and Culture::420300 Cultural Studies::420304 Screen and media studies